Det jämtländska bynamnet Helgebacken ur namntypologisk synvinkel: English: The Jämtland village name Helgebacken from a name typology perspective - Holm, Olof (Namn och bygd, 2022)
This article discusses the village name Helgebacken in the parish of Oviken, Jämtland, recorded since the beginning of the 16th century. The author notes that there was once a farm next to Helgebacken called Ungesvensbacken and Halvarsbacken. This farm lay deserted during the 16th century. Sources show that during the 15th century, these names were preceded by the simplex name Backen. The author interprets the compound names as originally being farm names of a type that was common in Jämtland during the Late Middle Ages, comprising a personal name and the name of the mother village. Helgebacken can therefore be interpreted as ‘Helge’s farm in Backen’.